Myocardial infarction in young women with special reference to oral contraceptive practice. - Mann, J I (1975)
Sixty-three women discharged from hospital with a diagnosis of myocardial infarction and 189 control patients were studied. All were under 45 years of age at the time of admission. Current oral contraceptive use, heavy cigarette smoking, treated hypertension and diabetes, pre-eclamptic toxaemia, and obesity were all reported by, and type II hyperlipoproteinaemia was found more often in, patients with myocardial infarction than their controls. The relationship between myocardial infarction and oral contraceptives could not be explained in terms of an association between the use of these preparations and the other factors. The combined effect of the risk factors was clearly synergistic.